PENERAPAN MEDIA PERMAINAN KARTU TABOO DALAM PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA JERMAN SISWA KELAS X BAHASA SMA NEGRI 1 DRIYOREJO - Detri Parut, Angela (LATERNE, 2017)
In German learning, especially speaking skiils, needs media that can help teachers and student improve their language skills. Taboo game is a game that demanding students or players to guess the word and formulate a sentence based upon words which was guessed/found. Statement of the problem of this research is how  the application of taboo game media in german language speaking skills of class X language program students  of SMAN 1 Driyorejo. The study aimed to describe the process of taboo game applications in speaking skills of class X language program students  of SMAN 1 Driyorejo . This is a  descriptive qualitative study. The data collected using research instrument. The instruments used in this research is observation form and students response questionnaire. The observation form used to asses student activity, and questionnaire used for asses student response after taboo game applied. The result of this study shows taboo game have positive response from students. This media motivated students to speak German. Observation form that have been used in this research indicated positive behavioral change in each meeting. Taboo Game can be applied in German language speaking skills. Key Words : Taboo Game, Speaking Skills